Characterization and implications of host‐cell protein aggregates in biopharmaceutical processing. Issue 4 (12th January 2023) - Oh, Young Hoon; Becker, Matthew L.; Mendola, Kerri M.; Choe, Leila H.; Min, Lie; Lee, Kelvin H.; Yigzaw, Yinges; Seay, Alexander; Bill, Jerome; Li, Xuanwen; Roush, David J.; Cramer, Steven M.; et al.
Abstract: In the production of biopharmaceuticals such as monoclonal antibodies (mAbs) and vaccines, the residual amounts of host‐cell proteins (HCPs) are among the critical quality attributes. In addition to overall HCP levels, individual HCPs may elude purification, potentially causing issues in product stability or patient safety. Such HCP persistence has been attributed mainly to biophysical interactions between individual HCPs and the product, resin media, or residual chromatin particles. Based on measurements on process streams from seven mAb processes, we have found that HCPs in aggregates, not necessarily chromatin‐derived, may play a significant role in the persistence of many HCPs. Such aggregates may also hinder accurate detection of HCPs using existing proteomics methods. The findings also highlight that certain HCPs may be difficult to remove because of their functional complementarity to the product; specifically, chaperones and other proteins involved in the unfolded protein response (UPR) are disproportionately present in the aggregates. The methods and findings described here expand our understanding of the origins and potential behavior of HCPs in cell‐based biopharmaceutical processes and may be instrumental in improving existing techniques for HCP detection and clearance.